Reduksi Keputusan Prokrastinasi Akademik Siswa melalui Teknik Pertanyaan Berskala dalam Konseling Ringkas Berfokus Solusi - Kharisma Gigih Kurniawan; Andi Mappiare AT; Adi Atmoko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
Academic procrastination is blocking on academic tasks. The students acted intentionally and often by waiting on initiating and finishing the tasks. In Solution-Focused Brief Counseling way, there is one approach namely scaling questions that can be apply to promoting reduce students behavior in deciding on academic procrastination. This research intends to figure out the difference level of academic procrastination between before and after therapy. This research using single subject design. We applying scaling questions technique and combine with Solution-Focused Brief Counseling to 5 students in Junior High School. The result of this research showed that there is a difference level of academic procrastination before and after the Solution-Focused Brief Counseling using scaling questions techniques was given. The implication of this research is Solution-Focused Brief Counseling using scaling questions techniques can be applied as another way by school counselors to encourage students to get out of academic procrastination issues.